Principles of dopant-free electron-selective contacts based on tunnel oxide/low work-function metal stacks and their applications in heterojunction solar cells. (April 2018) - Yang, Zhenhai; Gao, Pingqi; Sheng, Jiang; Tong, Hui; Quan, Cheng; Yang, Xi; Chee, Kuan W.A.; Yan, Baojie; Zeng, Yuheng; Ye, Jichun
Abstract: Dopant-free carrier-selective contacts (CSCs) are considerably attractive on highly efficient crystalline silicon (c-Si) based heterojunction solar cells (HSCs) owing to their combined advantages of low thermal budget, ease of processing and simplicity of the device architecture. However, due to inferior passivation property and relatively high resistivity, the silicon oxide (SiOx ) thin film is always ruled out as a viable interfacial layer in a CSC. Here, we demonstrate that the functionalization of nanoscale SiOx films with low work-function metals (WFMs) can simultaneously achieve moderate-level passivation and low contact resistivity on lightly doped n -type c-Si. Simulation results on the CSC comprising SiOx /low-WFM reveal that the tunnel SiOx layer alleviates Fermi-level pinning, and the low WFM helps to reduce the effective barrier height and contact resistivity. This kind of bi-functional electron-selective design possesses high tolerance to the surface state density on the c-Si surface as well as the SiOx layer thickness, as experimentally confirmed by the SiOx /Mg stack achieving an implied open-circuit voltage of 661 mV and a contact resistivity of 35.2 mΩ·cm 2 for a SiOx film thickness up to 1.7 nm. A comprehensive assessment suggests that this kind of rear electron transport layer (ETL) enables a theoretical power conversion efficiency ( PCE ) up to 27.4% if assuming an ideal front junction. Ultimately, a fully dopant-free c-Si HSC featuring a SiOx /low-WFM electron-selective contact and a MoOx hole-selective contact was proposed, yielding a PCE of 21.8%. The relatively high performance and facile integration with c-Si substrates enabled by the SiOx /low-WFM contact may open up new possibilities in designing and fabricating low-cost dopant-free SCs toward high efficiencies competitive with conventionally diffused pn junction SCs. Graphical abstract: The functionalization of dopant-free electron-selective contact (ESC) design based on nanoscale SiOx films capped with low work-function metals (WFMs) was demonstrated, which can simultaneously achieve moderate-level passivation and low contact resistivity on lightly doped n -type c-Si.fx1 Highlights: A high-performance dopant-free electron-selective contact design of SiOx/work-function metal design is proposed. The trade-offs in passivation and contact resistivity are thoroughly investigated experimentally and theoretically. High tolerance to the surface state density of Si surface and the SiOx layer thickness. The figure of merit and the efficiency limit for this kind of selective contact was predicted.